Analysis of Resistivity Anisotropy of Loaded Coal Samples - Xiangchun Li; Zhenxing An; Qi Zhang; Xiaolong Chen; Xinwei Ye; Suye Jia (Advances in Materials Science and Engineering)
In this paper, an experimental study of the variation of resistivity of coal samples in different bedding directions at 1 MHz frequency was performed by establishing an experimental system for resistivity testing of coal under triaxial stress. The low-pressure nitrogen gas adsorption (LP-N2GA) experiment and scanning electron microscopy (SEM) were obtained to analyze the pore-fracture structural characteristics of coal samples and the influence on resistivity anisotropy. Furthermore, the fundamental cause of anisotropy of coal resistivity is expounded systematically. The results show that the resistivity of loaded coal decreased first before increasing. The ionic conductance and the high degree of metamorphism slow down the decrease of resistivity. The distribution of pore and fracture structures is anisotropic. The connected pores and fractures are mainly distributed along the parallel bedding direction. The weak plane of bedding, diagenetic fractures, and plane fracture structures of parallel bedding result in the increase of fractures in the direction of vertical bedding, so increasing the potential barrier. Therefore, the resistivity in the vertical bedding direction is higher than that of the parallel bedding. Loading coal resistivity anisotropy degree is a dynamic change trend; the load increases anisotropy significantly under axial pressure, and the degree of anisotropy has a higher discreteness under confining pressure. It is mainly the randomness of the internal pore-fracture compaction, closure, and development of the heterogeneous coal under the confining pressure; the more rapid the decline in this stage, the larger the stress damage degree.